1999
DOI: 10.1289/ehp.99107s5749
|View full text |Cite
|
Sign up to set email alerts
|

Linking iodine with autoimmune thyroiditis.

Abstract: A great deal of circumstantial evidence has linked iodine with the rising incidence of autoimmune thyroiditis in the United States. In our investigations, we have shown directly that T cells from humans with chronic lymphocytic thyroiditis proliferate in the presence of iodinated but not in the presence of noniodinated human thyroglobulin. Moreover, the proliferative response is restored when the thyroglobulin is iodinated artificially in vitro. Using a panel of monoclonal antibodies, we found evidence that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 28 publications
3
51
1
4
Order By: Relevance
“…Recently, it has been reported that hsp60 cross-reactive T cells mediate autoimmune pathology of the small intestine (29). In contrast to the above-mentioned studies (11)(12)(13)(14)(15)(16), in this study, we attribute reduced incidence and severity of, rather than induction of, AA to determinant mimicry.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Recently, it has been reported that hsp60 cross-reactive T cells mediate autoimmune pathology of the small intestine (29). In contrast to the above-mentioned studies (11)(12)(13)(14)(15)(16), in this study, we attribute reduced incidence and severity of, rather than induction of, AA to determinant mimicry.…”
Section: Discussioncontrasting
confidence: 57%
“…In other experimental animal models of autoimmunity, the initiation and/or propagation of autoimmunity has been attributed to the conventional environment; for example, joint and intestinal inflammatory disease in HLA-B27 transgenic rats (12), iodine-induced autoimmune thyroiditis in NOD-H2 h4 mice (13), experimental autoimmune thyroiditis in rats (14), hemolytic anemia (15), experimental autoimmune encephalomyelitis (16), and Pristaneinduced arthritis (17). In contrast, the current study has revealed that exposure of a susceptible rat strain to the conventional environment rather leads to a significant reduction in the incidence and severity of an autoimmune disease, AA, through spontaneous induction of T cells against regulatory determinants of Bhsp65.…”
mentioning
confidence: 99%
“…Our favorable findings, however -no rise of average antibody titers and no rise of the percentage of titers found above the normal limit, but rather a decrease of all anti-Tg-Ab titers -contrast with data from elsewhere, where the increment in iodine supply had been steeper. Experimentally, the steep rise of iodine supply in genetically susceptible mice caused a higher occurrence of autoimmune thyroiditis and of positive anti-Tg-Ab titers in a dosedependent manner after only 8 weeks (Rose et al, 1997). In Sri Lanka, the prevalence of anti-Tg-Ab was found markedly raised (14.3-69.7%) in 367 schoolgirls aged 11-16 y, after commercial salt had been iodized at a variable degree in 1993 (Premawardhana et al, 2000).…”
Section: Auto-antibodiesmentioning
confidence: 99%
“…Autoimmune thyroiditis is characterized by lymphocytic infiltration and generation of autoantibodies that recognize thyroidrelated molecules including thyrotropin and its receptors, the Na-I symporter (rNIS), thyroglobulin, T3, and T4 (8,11,12 (Table 2).…”
Section: Iodinementioning
confidence: 99%